THE MODERN SYSTEM OF CRIMINAL PROCEDURAL LAW OF THE REPUBLIC OF KAZAKHSTAN: PROBLEMS OF REGULATING THE STAGES OF PROCEEDINGS (Journal of actual problems of jurisprudence, 2024)
Criminal procedural law of the Republic of Kazakhstan, like any other independent fundamental branch, initially has its own system. Modernization of the methodology of criminal procedural law, implemented in the current CPC RK, has led to radical changes in the structure of the previously established system. The system, which was understood as a consistent set of stages of criminal proceedings, to a certain extent has lost the signs that indicated the existence of specific stages. Individual stages have lost their clear outlines, which began to manifest itself in violation of the logical sequence of actions and decisions of procedural nature.The article considers the general concept of criminal justice system, its modern transformational model and the place of procedural stages in it. Modernization of law enforcement system and reforming of criminal prosecution bodies are the most important and urgent priorities in the national legal policy. Reform processes are reflected in the state of criminal procedure system.Preservation and improvement of the system of criminal proceedings is a specific guarantee of presence in it of a logical sequence of legal relations developed between subjects, and also observance of legality at all stages and phases of criminal proceedings.The paper formulates the framework proposals aimed at improving the system of criminal procedural law of Kazakhstan.Keywords: system of criminal procedural law, stages of criminal proceedings, guarantees of compliance with the rule of law, administration of criminal justice.